Efektivitas Penerapan Metode Talking Stick Dalam Pembelajaran Keterampilan Menulis Teks Tanggapan Kritis - Andriani Andriani; Fausiah Fausiah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2018)
The background of this research is due to the lack of ability to write learners in Indonesian language learning, especially in writing critical response text. This research is an experimental research that aims to get an idea of the effectiveness or not of the learning method of talking stick in the Indonesian language lesson, especially writing the text of critical responses in class IX students of SMP Negeri 6 Wonomulyo. Based on the result of the research, using descriptive statistical analysis for the instrument in the form of the result of the pretest learning test of class IX D as experiment class before the application of the talking stick method obtained an average value of 2.33% and after the application of talking stick method in learning writing critical text responses the average posttest score increased by 3.20%. While in class IX B as control class pretest average value of 2.22% and after the use of conventional methods final or posttest test results average value of 2.91%. Result of inferential statistic analysis for hypothesis test by using Independent Samples Test obtained sig value 0,312> 0,05, so H0 rejected. From the results of this study can be concluded that there are differences of learners who were taught by using conventional methods and learners who are given special treatment by applying the talking stick method, in this case it is known that Indonesian language learning with talking stick method is effective compared to learning Indonesian language with conventional method (not given treatment)